ChemInform Abstract: Tertiary α‐Diarylmethylamines Derived from Diarylketimines and Organomagnesium Reagents. Issue 23 (June 2015) - Desmarchelier, Alaric; Ortiz, Pablo; Harutyunyan, Syuzanna R.
Abstract 18 examples